Critical Thinking and Effective Personality in the Framework of Education for Sustainable Development - Gladys Merma-Molina; Diego Gavilán-Martín; Salvador Baena-Morales; Mayra Urrea-Solano (MDPI AG, 2022)
According to UNESCO, critical thinking (CT) is a strategic skill for the 21st century, as it is associated with attitudes of personal and social change and improvement. Based on this, the objectives of this study were (1) to find out the possible relationships between CT and effective personality (EP) and (2) to determine the extent to which EP predicts the development of CT in children and adolescents. The research approach was quantitative, correlational and predictive. The sample consisted of 562 Spanish students. The measurement instruments were: (1) the Critical Thinking Disposition Inventory and (2) the Efficacy Personality Questionnaire. The main findings showed that there is a positive relationship between EP and CT, with the traits "being enthusiastic", "developing positive self-esteem" and "having self-confidence" correlating most strongly with CT. The regression analysis shows that EP influences the development of students' CT. There were no significant differences according to sex, and Primary Education students obtained higher CT scores. It is concluded that the better the promotion of EP, the greater the CT development will be. This suggests the need to design educational programmes for the improvement of EP, especially in adolescents.